Propuesta de una Herramienta de Gestión de Responsabilidad Social en Proyectos de Construcción - Godínez-Salazar, Natalia (Instituto Tecnológico de Costa Rica, 2015)
The contexts that can be present on construction projects are: areas with presence of biodiversity, range of stakeholders (from communities to government entities), difficult working conditions, legal regulations and sets of different natures providers, such as subcontracting for construction services and materials. This makes important to incorporate Corporate Social Responsibility (CSR) practices in construction projects in a methodical way, to obtain the expected results for the project that will benefit the competitiveness of the organization and integrate issues involving sustainable human development. The overall objective of this project was to design a proposal for a management tool to integrate best practices of CSR in construction projects This tool is based on standard ISO 26000 Guide on Social Responsibility, established by the International Organization for Standardization (ISO) and the processes established by the Guide to the Project Management Body of Knowledge and the Construction Extension, proposed by Project Management Institute ( PMI). This resulted in four macroprocesses: Setting the Context, Planning, Operational Control and Review. Were obtained in total 29 among the four processes macroprocesses; each of the processes inputs, outputs and tools are assigned; the tools and techniques were obtained through literature and interviews three experts. so user expertise will find the characteristic for the type of project that requires building. The 29 proposed process are associated to Guide to the Project Management Body of Knowledge and the Construction Extension, approximately 76 % were related to the Area of Knowledge Project Environmental Management with the different Process Groups, according to the particularity of project could identify more interactions, these are must integrate CSR programs to unify the efforts of project management and management of CSR. The core subjects and relevant issues were proposed within each macro process, but a more detailed review to elaborate on other CSR issues may be relevant to the particularity construction projects types. The proposed tool was validated by an expert on CSR. The management tool to integrate best practices of social responsibility in construction projects, was reviewed by an expert in CSR, the review was proven by a written letter.
Proyecto de Graduación (Maestría en Gerencia de Proyectos). Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2015.
Keywords: Construcción; Biodiversidad; ISO 26000; RSE; Desarrollo humano